2009
DOI: 10.1002/jobm.200900085
|View full text |Cite
|
Sign up to set email alerts
|

Multiresistant Vibrio cholerae non‐O1/non‐O139 from waters in South India: resistance patterns and virulence‐associated gene profiles

Abstract: From different aquatic locations in Alleppey district, Kerala, South India a number (n = 36) of multiresistant non-O1, non-O139 V. cholerae strains were isolated. Water samples were filtered through 0.22 µm membrane filters, enriched in alkaline peptone water and plated onto thiosulfate-citrate-bile salts-sucrose (TCBS) agar. The isolates were resistance to cefotaxime (50%), nalidixic acid (44.4%), streptomycin and tetracycline (41.6%), trimethoprim (38.8%), cotrimoxazole (33.3%), furazolidone (27.7%), neomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Previous studies have shown that sporadic cholera isolates may carry VPI or both VPI and CTX factors [12], [19]–[21]. Rtx toxin, T3SS and NAG-ST have also been reported to contribute to their virulence [27]–[29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that sporadic cholera isolates may carry VPI or both VPI and CTX factors [12], [19]–[21]. Rtx toxin, T3SS and NAG-ST have also been reported to contribute to their virulence [27]–[29].…”
Section: Resultsmentioning
confidence: 99%
“…However, many non-O1/non-O139 strains have been found to carry one or both virulence factors [12], [19]–[21]. Some strains such as the O141 strains carry both Vibrio Pathogenicity Island (VPI) and cholera toxin phage (CTXΦ) [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that, even in the absence of these virulence genes, non-O1 and non-O139 V. cholerae can cause diarrhea similar to cholera 18 , but do not generate epidemics. Many cases of diarrhoeal diseases related to non-O1 and non-O139 V. cholerae were reported 2,7,21,26 .…”
Section: Resultsmentioning
confidence: 99%
“…We detected 23.5% of resistance to cefotaxime in V. parahaemolyticus from sea turtles, a similar prevalence of resistance to cefotaxime (20%) has also been reported in strains isolated in Italy from shellfish and clinical samples (Ottaviani et al, 2013 ). A number of studies have been reported low (Ceccarelli et al, 2015 ) and high (Jagadeeshan et al, 2009 ) prevalence of V. cholerae non-O1/non-O139 strains resistant to numerous antibiotics, isolated from environmental samples. In this study, only a few of the non-O1/non-O139 V. cholerae isolates from sea turtles were resistant to ampicillin or gentamicin.…”
Section: Discussionmentioning
confidence: 99%